Paving the way to ultra-fast fashion: an exploratory research - Camargo, Lucas Ramos (2018)
This research study focuses on a new concept in fashion called ultra-fast fashion. As being underresearched, there is an opportunity for an exploration of what this new concept is, examine its possible differences and similarities with the well-developed business model called fast-fashion, and determine if ultra-fast fashion is a new business model or a mere new segment in fashion. This study took a qualitative approach, using document analysis and in-depth interviews with industry specialists. After conducting a document analysis of secondary data and collecting indepth interviews, our main results indicate that ultra-fast fashion can be seen as a potential new business model in fashion following a faster supply chain strategy to attend to consumer demands in an innovative way. Ultra-fast fashion has a direct-to-consumer business model with a focus on producing clothes on an on-demand basis, and higher data-reliance mainly collected through a vertically-integrated e-commerce. In addition, ultra-fast fashion’s supply chain strategy mainly avoids excess inventory, focuses on local manufacturing, on-demand production, shorter lead times of a few days to a week with a combination of agile, lean, and responsive supply chain strategies.